Ethnopedagogy-based Thematic Modules to Improve the Understanding and Cultural Literacy of Elementary School Students - Dafit, Febrina; Ramadan , Zaka Hadikusuma; Anggriani, Mitha Dwi (International Journal of Elementary Education, 2024)
The decline in students' local cultural knowledge and the decline in the level of understanding of students' concepts in thematic learning are problems that need to be overcome. This study aimed to develop a thematic learning module based on ethnopedagogy to enhance understanding and cultural literacy of the fifth-grade elementary school students. This research utilized an R&D method adopting the ADDIE model, which consisted of five stages (Analysis, Design, Development, Implementation, and Evaluation). The instrument used to collect data in this study was a questionnaire. This questionnaire was given to several experts, such as the design experts, material experts, and language experts, to see the feasibility of the module as well as the teachers’ and students’ responses to see the practicality of the module. Then, a test and a questionnaire were administered to examine the effect of the ethnopedagogy-based thematic learning module on students' understanding and cultural literacy. The data were then analyzed both qualitatively and quantitatively. Furthermore, the effectiveness of the module was analyzed using Multivariate Analysis of Variance (Manova). This study suggested that the ethnopedagogy-based thematic learning module fulfilled the very feasible criteria with an average score of 93.61% from the design validator, 93.26% from the material validator, and 91% from the language validator. Furthermore, from the response given by the teachers, a score of 92.65% was obtained with a very attractive category. Then, the small-scale trial conducted on students obtained a score of 96.67% with a very attractive category. Apart from that, the thematic learning module based on ethnopedagogy was also able to improve the understanding and cultural literacy of the fifth-grade elementary school students, as proven by the results of the product effectiveness test using the Manova test which obtained a significance value of 0.00 < 0.05.